2021
DOI: 10.1016/j.molmet.2021.101178
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of mitochondrial uncouplers for the treatment of metabolic associated fatty liver disease and NASH

Abstract: Background Mitochondrial uncouplers shuttle protons across the inner mitochondrial membrane via a pathway that is independent of adenosine triphosphate (ATP) synthase, thereby uncoupling nutrient oxidation from ATP production and dissipating the proton gradient as heat. While initial toxicity concerns hindered their therapeutic development in the early 1930s, there has been increased interest in exploring the therapeutic potential of mitochondrial uncouplers for the treatment of metabolic diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 130 publications
1
35
0
Order By: Relevance
“…Some of the beneficial effects of mild mitochondrial uncoupling have previously been attributed to activation of AMPK and alterations in mitochondrial biogenesis (Demine et al, 2019 ; Goedeke & Shulman, 2021 ). To determine whether CRMP‐mediated reductions in ectopic lipid content and improvements in hepatic insulin sensitivity were due to mitochondrial adaptations, we next evaluated the effects of CRMP treatment on several static markers of mitochondrial content in the livers of HFD‐fed aging mice treated with 20 mg/(kg‐day) CRMP for 4 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the beneficial effects of mild mitochondrial uncoupling have previously been attributed to activation of AMPK and alterations in mitochondrial biogenesis (Demine et al, 2019 ; Goedeke & Shulman, 2021 ). To determine whether CRMP‐mediated reductions in ectopic lipid content and improvements in hepatic insulin sensitivity were due to mitochondrial adaptations, we next evaluated the effects of CRMP treatment on several static markers of mitochondrial content in the livers of HFD‐fed aging mice treated with 20 mg/(kg‐day) CRMP for 4 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have indicated that a reduction of the hepatic mitochondrial function and abnormalities of lipid metabolism are associated with increases in ectopic fat deposition and insulin resistance in humans with MAFLD [ 42 , 43 , 44 , 45 ]. In particular, mitochondrial dysfunction includes impaired oxidative phosphorylation (OXPHOS), and increased production of ROS [ 46 ]. A gene expression analysis suggested that the observed mitochondrial dysfunction might be attributable to the downregulation of genes related to the mitochondrial quality control, which has been demonstrated to operate through the coordination of biogenesis, dynamics, and mitophagy to ensure cell homeostasis [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome its adverse effects, the liver-targeted agents DNP-methyl ether (DNPME) and controlled-release mitochondrial protonophore (CRMP) were developed. Both agents enhance hepatic FAO and reduce ectopic lipid deposition without changes in BW, resulting in improved hepatic steatosis and whole-body IR in rodent models and nonhuman primates [148]. Conversely, BAM15 decreases BW without affecting food intake, and improves whole-body insulin sensitivity, hepatic FAO, steatosis and inflammation in obese mice [148].…”
Section: Modulation Of Lipid and Energy Metabolismmentioning
confidence: 99%